Crescentic Glomerulonephritis: Pathogenesis and Therapeutic Potential of Human Amniotic Stem Cells - Al Mushafi, Ahmed; Ooi, Joshua D.; Odobasic, Dragana (Frontiers in Physiology, 2021)
Chronic kidney disease (CKD) leads to significant morbidity and mortality worldwide. Glomerulonephritis (GN) is the second leading cause of CKD resulting in end stage renal failure. The most severe and rapidly progressive type of GN is characterised by glomerular crescent formation. The current therapies for crescentic GN, which consist of broad immunosuppressive drugs, are partially effective, non-specific, toxic and cause many serious side effects including infections, cancer and cardiovascular problems. Therefore, new and safer therapies are needed. Human amniotic epithelial cells (hAECs) are a type of stem cell which are isolated from the placenta after birth. They represent an attractive and novel therapeutic option for the treatment of various inflammatory conditions owing to their unique and selective immunosuppressive ability, as well as their excellent safety profile and clinical applicability. In this review, we will discuss the immunopathogenesis of crescentic GN, issues with currently available treatments and how hAECs offer potential to become a new and harmless treatment option for this condition.